Hyperbaric Oxygen Effects on Contrast and Macular Light Sensitivity in Dry Type Age-Related Macular Degeneration Patients - Dewi, Indriani Kartika; Moestidjab, Moestidjab; Harnanik, Titut (Folia Medica Indonesiana, 2021)
This study was to compare the effectiveness of hyperbaric oxygen therapy (HBOT) on contrast and macular light sensitivity improvement in dry type age-related macular degeneration (AMD) patients. The subjects were eyes that had been diagnosed with dry type AMD which met inclusion criteria. The subjects were divided into two groups. The first group was given antioxidants and HBOT. The second group was given only antioxidants. Contrast and macular light sensitivity test were done using MARS contrast sensitivity chart and Humphrey Field Analyzer-3 for three times, pre-therapy, day-1 and 14 post- therapy. This study found that 25 eyes were included for analysis, 14 subjects in first group, and 11 subjects in second group. Statistical analysis results showed that there were significant increase on contrast sensitivity in intervention group between one-day post-therapy with pre-therapy, P = 0.003 (P <0.05), and between 14-days post-therapy with pre-therapy, P = 0,015 (P <0.05). From pre- and post-analysis, there were no significant difference found on contrast sensitivity in control group and macular light sensitivity in intervention group. In control group, there were significant increase on superotemporal, superonasal, and inferonasal area between one-day post-therapy and pra-therapy with P = 0.004, P = 0.013 and P = 0.008 (P <0.05), respectively, and there was significant decrease on inferonasal area between 14-days post-therapy and one-day post-therapy, P = 0.003 (P <0.05). In conclusion, patients with AMD who were subjected to HBOT achieved improvement in contrast sensitivity in cases considered as having low prognosis. HBOT should be considered as promising intervention for AMD management adjuvant and further research are needed to find optimal dosage.